Hematological Parameter-Derived Inflammatory Scores in Non-Pancreatic Hyperlipasemia (NPHL)—The Prognosis Lies in the Blood - Krisztina Eszter Feher; David Tornai; Maria Papp (Biomedicines, 2025)
Background/Objectives: Non-pancreatic hyperlipasemia (NPHL) is associated with high in-hospital mortality, with sepsis being one of the most common etiologies. The prognostic value of hematological parameter-derived inflammatory scores has not been extensively studied in NPHL to date. Methods: The prognostic value of eight inflammatory scores for in-hospital mortality was assessed in a total of 545 NPHL patients from two hospitalized patient cohorts (COVID-19 [n = 144] and non-COVID-19 [n = 401], the latter stratified as bacterial sepsis [n = 111] and absence of systemic infection [n = 290]). We assessed the neutrophil-to-lymphocyte ratio (NLR), derived NLR (dNLR), neutrophil-to-lymphocyte and platelet ratio (N/(LP)), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), aggregate index of systemic inflammation (AISI), systemic inflammation index (SII), and systemic inflammation response index (SIRI), comparing their prognostic value among etiological groups. Results: Patients with bacterial sepsis were older, had more comorbidities, and experienced worse outcomes, including longer hospitalization (median: 15, 7, and 11 days; p < 0.001), higher ICU admission rates (75.7%, 33.8%, and 47.9%, p < 0.001), and increased mortality (45.0%, 13.8%, and 38.2%, p < 0.001), compared to those without systemic infection or with COVID-19-induced NPHL. Overall, NLR, dNLR, and N/(LP) were the most accurate predictors of in-hospital mortality at admission (AUROC: non-infection: 0.747; 0.737; 0.772; COVID-19: 0.810; 0.789; 0.773, respectively). The accuracy of NLR decreased in bacterial sepsis, and only N/(LP) and PLR remained associated with in-hospital mortality (AUROC: 0.653 and 0.616, respectively). Conclusions: The prognostic performance of hematological parameter-derived inflammatory scores in NPHL is etiology-dependent. NLR is the most accurate prognostic tool for mortality in the absence of bacterial sepsis, while N/(LP) is the best score in sepsis-induced NPHL.